Model‐based determination of the influence of textile fabric on bioassay analysis and the effectiveness of a textile slow‐release system of DEET in mosquito control. Issue 8 (15th October 2014) - Malengier, Benny; Goessens, Tineke; Mafo, Flora F; De Vrieze, Mike; Van Langenhove, Lieva; Wanji, Samuel; Lynen, Frederic
Abstract BACKGROUND Determining the effectiveness of a product in repelling mosquitoes or other flying insects is a difficult task. One approach is to use a bioassay with textile fabric. We investigated the role of the textile substrate in a bioassay with a numerical model, and compared the outcome with known results for DEET. The model was then used to determine the effectiveness of textile slow‐release formulations based on coatings, and results were compared with those of a field study in the Cameroon. Slow‐release formulations are difficult to evaluate with standard tests, as the compound needs a build‐up time not present in these tests. RESULTS We found excellent correspondence between the model and the known DEET results without matching parameters. Slow‐release approaches are deemed possible but have several drawbacks. Modelling can help in identifying optimal use conditions. The field test with a slow‐release system performed better than anticipated by the model, with initially more than 90% repellency. DEET‐coated textile was considered not to be marketable, however. CONCLUSION We advise that bioassays characterise in more detail the type of textile fabric used so as to allow conclusions to be drawn by textile modelling. As regards coated‐textile slow‐release systems, more research is needed. We nevertheless advise usage mainly at entry points, e.g. as scrims. © 2014 Society of Chemical Industry